2018
DOI: 10.1177/1744806918797042
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, electrophysiological, and cutaneous innervation changes in patients with bortezomib-induced peripheral neuropathy reveal insight into mechanisms of neuropathic pain

Abstract: Bortezomib is a mainstay of therapy for multiple myeloma, frequently complicated by painful neuropathy. The objective of this study was to describe clinical, electrophysiological, and pathological changes of bortezomib-induced peripheral neuropathy (BiPN) in detail and to correlate pathological changes with pain descriptors. Clinical data, nerve conduction studies, and lower leg skin biopsies were collected from 22 BiPN patients. Skin sections were immunostained using anti-protein gene product 9.5 (PGP9.5) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 71 publications
(133 reference statements)
0
32
0
Order By: Relevance
“…Increased thermal and mechanical detection thresholds derived from quantitative sensory testing reflect the dysfunction of A-beta-, A-delta-, and C-fibers [68]. Histological findings of early BIPN stages demonstrate axonal swelling rather than a diminished intraepidermal nerve fiber density in skin biopsies [66]. Thalidomide and bortezomib combination therapies can lead to a more prominent, reversible, length-dependent, sensory rather than motor, and predominately axonal, large-fiber more than small-fiber polyneuropathy [70].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Increased thermal and mechanical detection thresholds derived from quantitative sensory testing reflect the dysfunction of A-beta-, A-delta-, and C-fibers [68]. Histological findings of early BIPN stages demonstrate axonal swelling rather than a diminished intraepidermal nerve fiber density in skin biopsies [66]. Thalidomide and bortezomib combination therapies can lead to a more prominent, reversible, length-dependent, sensory rather than motor, and predominately axonal, large-fiber more than small-fiber polyneuropathy [70].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Median pain intensity and the McGill pain questionnaire sum score point towards a moderate to severe neuropathic pain within BIPN. In a recent study, up to 77% of patients with MM had a mean pain intensity > 4 (numerical rating scale; 0 = "no pain" to 10 = "most intense pain imaginable") [66]. Grade 1 or 2 BIPN can occur in up to 75%, and Grade 3 or 4 BIPN in 30% of newly diagnosed MM patients [68].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…90 Skin biopsy demonstrates nonspecific findings of reduction in subepidermal nerve fiber density and increased axonal swelling. 91 Neuropathy generally occurs after the fifth cycle of treatment with a cumulative dose of 42 mg/m 2 . A randomized trial has shown that subcutaneous administration of bortezomib was associated with a lower rate of neuropathy compared with intravenous administration.…”
Section: Taxanesmentioning
confidence: 99%